Rubber composition and tire
Patent Information
- Application Number
- JP2021550654
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-02
- Filing Date
- 2020-09-23
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-09-23
AI Technical Summary
【0016】 本発明によれば、ブタジエンゴム及び/又はスチレンブタジエンゴムを含み、かつ、水によって可逆的に複素弾性率E*が変化し、前記式(1)~(3)を満たすゴム組成物であるので、ウェット性能、ドライ性能の総合性能を改善できる。
Smart Images

Figure 0007639689000001 
Figure 0007639689000002 
Figure 0007639689000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition and a tire. [Background technology]
[0002] In recent years, as a common issue for automobiles, awareness of safety has been increasing, and further improvement in wet grip performance is required. Various studies have been conducted so far to improve wet grip performance, and various inventions of rubber compositions containing silica have been reported (for example, Patent Document 1). Since wet grip performance is greatly influenced by the performance of the rubber composition, particularly in the tread portion that contacts the road surface, technical improvements in rubber compositions for tires such as treads have been widely studied and put into practical use. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-285524 A Summary of the Invention [Problem to be solved by the invention]
[0004] As a result of intensive research by the present inventors, it was found that while significant progress has been made in the wet grip performance of tires due to technical improvements in rubber compositions for treads using silica, the change in grip performance when the road surface changes, for example, from a dry road surface to a wet road surface, or from a wet road surface to a dry road surface, remains an important technical issue and there is room for improvement. As a result of intensive research by the present inventors, it was found that conventional rubbers have a property that when they change from a dry state (not wet with water) to a so-called wet state (wet state), their hardness does not change or they become hard when cooled by water, so that the contact area with the road surface decreases, and as a result, the wet grip performance tends to be lower than the dry grip performance. It was also found that for the same reason, the steering stability in a wet state tends to decrease. As a method for improving wet performance, a method of softening the rubber by blending a softener is known, but it was also found that softening the rubber causes a problem of worsening the rolling resistance on a dry road surface. As such, it has become clear that there is room for improvement in conventional technology in terms of comprehensively improving wet performance (wet grip performance, etc.) and dry performance (dry grip performance, rolling resistance on dry roads, etc.). An object of the present invention is to provide a rubber composition and a tire that can solve the above problems and improve the overall performance, including wet performance and dry performance. [Means for solving the problem]
[0005] The present invention relates to a rubber composition which contains butadiene rubber and / or styrene-butadiene rubber, has a complex modulus E* which reversibly changes with water, and satisfies the following formulas (1) to (3). Formula (1) Complex modulus of elasticity E* when wetted with water / Complex modulus of elasticity E* before wetted with water × 100≦98 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (2) 99≦Complex modulus of elasticity E* after drying / Complex modulus of elasticity E* before wetting with water × 100≦100 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (3) 99≦Volume when wetted / Volume before wetted×100≦100 (In the formula, the volume is the volume of the rubber composition at 23°C.)
[0006] In the rubber composition, it is preferable that a part or all of the rubber molecules of the rubber component are crosslinked by ionic bonds.
[0007] It is preferable that the rubber composition contains 1.0 part by mass or more of at least one selected from the group consisting of carbon black and silica based on 100 parts by mass of the rubber component.
[0008] It is preferable that the rubber composition contains 15 to 70 parts by mass of silica based on 100 parts by mass of the rubber component.
[0009] It is preferable that the rubber composition contains at least one selected from the group consisting of carboxylic acid-modified styrene-butadiene rubber and carboxylic acid-modified butadiene rubber, and a compound having at least one selected from the group consisting of a metal element, a metalloid element, and a nitrogen element.
[0010] It is preferable that the resin is contained in an amount of 1 to 50 parts by mass based on 100 parts by mass of the rubber component.
[0011] It is preferable that the plasticizer is contained in an amount of 15 parts by mass or more based on 100 parts by mass of the rubber component.
[0012] It is preferable that the contents of silica and plasticizer per 100 parts by mass of the rubber component satisfy the following formula. Plasticizer content / Silica content<1.0
[0013] It is preferable that the contents of silica and resin per 100 parts by mass of the rubber component satisfy the following formula. Resin content / Silica content<1.0
[0014] It is preferably a rubber composition for a tread.
[0015] The present invention also relates to a tire having a tire component at least partially constituted by the rubber composition. Effect of the Invention
[0016] According to the present invention, the rubber composition contains butadiene rubber and / or styrene-butadiene rubber, the complex modulus E* of the rubber reversibly changes with water, and satisfies the above formulas (1) to (3), thereby improving the overall wet and dry performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The rubber composition of the present invention contains butadiene rubber and / or styrene-butadiene rubber, has a complex modulus E* that reversibly changes with water, and satisfies the following formulas (1) to (3), thereby improving the overall wet and dry performance. Formula (1) Complex modulus of elasticity E* when wetted with water / Complex modulus of elasticity E* before wetted with water × 100≦98 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (2) 99≦Complex modulus of elasticity E* after drying / Complex modulus of elasticity E* before wetting with water × 100≦100 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (3) 99≦Volume when wetted / Volume before wetted×100≦100 (In the formula, the volume is the volume of the rubber composition at 23°C.)
[0018] The problem (objective) of the present invention is to improve the overall performance of wet performance (wet grip performance, etc.) and dry performance (dry grip performance, rolling resistance in dry conditions, etc.), and the means for solving this problem is to configure a rubber composition containing styrene butadiene rubber (SBR) and / or butadiene rubber (BR) so that the complex modulus E* changes reversibly with water and satisfies the above formulas (1) to (3). That is, the essential feature of the present invention is to configure a rubber composition containing SBR and / or BR so that the complex modulus E* changes reversibly with water and satisfies the above formulas (1) to (3).
[0019] The above-mentioned rubber composition provides the above-mentioned effects, and although the reason why such effects are obtained is not entirely clear, it is presumed to be as follows. The present invention relates to a rubber composition containing SBR and / or BR as a rubber component, in which the complex modulus E* is reversibly changed by water and satisfies the above formulas (1) and (2). Here, the above formula (1) means that the E* of the rubber composition when wetted with water drops to 98% or less, relative to the E* (100%) of the rubber composition before wetted with water (rubber composition at the time of initial drying before wetted with water). Furthermore, the above formula (2) means that the E* of the rubber composition after wetted with water and further re-dried returns to the range of 99 to 100%, relative to the E* (100%) of the rubber composition before wetted with water. In other words, the rubber composition of the present invention has a complex modulus E* that reversibly changes due to water and satisfies the above formulas (1) and (2). This means that the complex modulus (E*) when swollen with water becomes smaller than the complex modulus (E*) when initially dried before wetting with water, and the complex modulus (E*) after re-drying largely returns to its original state, and E* changes reversibly in the presence of water. Therefore, when the road surface changes from dry to wet, the rubber composition is wetted with water, the complex modulus E* of the rubber composition decreases, the deterioration of wet grip performance is suppressed, and good wet performance is obtained. This is because, since wet roads are slippery, sufficient grip performance cannot be obtained with E* that is suitable for dry roads, but by decreasing E*, the contact area with the road surface increases, the deterioration of wet grip performance can be suppressed, and good wet performance (wet grip performance, etc.) can be obtained. On the other hand, when the road surface changes from wet to dry, the rubber composition moistened with water dries and the E* of the rubber composition increases (returns), so that the rolling resistance during driving on dry roads is maintained and good fuel economy can be ensured. In addition, the decrease in dry grip performance can be suppressed, and good dry grip performance can be obtained. This is because the tire is not likely to slip on dry roads, so sufficient grip performance cannot be obtained if the E* is kept at a level suitable for wet roads. However, it is presumed that the increase in E* makes the tire suitable for dry roads, suppressing the decrease in dry grip performance and obtaining good dry grip performance. In this way, by containing SBR and / or BR, and by having the complex modulus E* change reversibly with water and satisfying the above formulas (1) and (2), an appropriate complex modulus (E*) and rolling resistance can be obtained according to the road surface condition (wet road surface, dry road surface), thereby improving wet performance and dry performance.
[0020] In addition, the rubber composition satisfies the above formula (3), and the volume of the rubber composition when wetted with water is 99 to 100% of the volume (100%) of the rubber composition before wetting with water (the rubber composition at the time of initial drying before wetting with water). Since the change in volume before and after wetting with water is small, adverse effects on other physical properties such as abrasion resistance, driving stability, and fuel economy can be suppressed.
[0021] Therefore, a rubber composition that contains SBR and / or BR, has a complex modulus E* that reversibly changes with water and satisfies the above formulas (1) to (3), can improve the overall performance of wet performance (wet grip performance, etc.) and dry performance (dry grip performance, rolling resistance in dry conditions, etc.).
[0022] In this specification, the complex modulus (E*) and volume of a rubber composition refer to the E* and volume of the rubber composition after vulcanization.
[0023] In this specification, "the complex modulus E* changes reversibly due to water" means that the complex modulus E* of the rubber composition (after vulcanization) reversibly increases or decreases due to the presence of water. For example, when changing from dry to wet to dry, the complex modulus E* only needs to change reversibly, and the complex modulus E* does not need to be the same at the first drying time and the second drying time, or may be the same at the first drying time and the second drying time.
[0024] In this specification, the complex modulus E* before wetting with water means the complex modulus E* of a rubber composition (after vulcanization) in a state that is dried before wetting with water, and specifically means the complex modulus E* of a rubber composition (after vulcanization) that is dried before wetting with water by the method described in the examples. In this specification, the complex modulus E* when wetted with water means the complex modulus E* of a rubber composition (after vulcanization) in a state wetted with water, and specifically means the complex modulus E* of a rubber composition (after vulcanization) wetted with water by the method described in the Examples. In this specification, the complex modulus E* after drying with water means the complex modulus E* of a rubber composition (after vulcanization) obtained by re-drying a rubber composition (after vulcanization) in a water-wet state, and specifically means the complex modulus E* of a rubber composition (after vulcanization) obtained by re-drying a rubber composition (after vulcanization) that has been wet with water by the method described in the Examples.
[0025] In addition, in this specification, the volume before wetting with water means the volume of the rubber composition (after vulcanization) in a state that is dried before wetting with water, and specifically means the volume of the rubber composition (after vulcanization) that is dried before wetting with water by the method described in the examples. In this specification, the volume when wet with water means the volume of the rubber composition (after vulcanization) in a state wet with water, and specifically means the volume of the rubber composition (after vulcanization) wetted with water by the method described in the examples.
[0026] In this specification, the complex modulus E* of a rubber composition (after vulcanization) is measured on a test vulcanized rubber sheet using a TA Instruments RSA-GII under conditions of a strain of 0.25%, a frequency of 10 Hz, and a temperature of 23°C.
[0027] In this specification, the volume of a rubber composition (after vulcanization) means, in the case of a rectangular parallelepiped, the volume calculated from the length, width and thickness measured in an environment of 23°C.
[0028] As shown in the above formula (1), the complex modulus E* when wet with water / complex modulus E* before wet with water × 100 (E* of the rubber composition (after vulcanization) when wet with water / E* of the rubber composition (after vulcanization) before wet with water × 100) is 98 or less, preferably 96 or less, more preferably 94 or less, even more preferably 93 or less, particularly preferably 92 or less, most preferably 91 or less, and may be 90 or less. By making it equal to or greater than the lower limit, the contact area with the road surface is improved, so that the deterioration of grip performance tends to be suppressed. The lower limit is not particularly limited, but is preferably 50 or more, more preferably 70 or more, and even more preferably 75 or more. When it is within the above range, the effect can be preferably obtained.
[0029] As shown in the above formula (2), the complex modulus E* after drying with water / complex modulus E* before wetting with water × 100 (E* of the rubber composition (after vulcanization) after drying with water / E* of the rubber composition (after vulcanization) before wetting with water × 100) is 99 or more and 100 or less. When it is within the above range, the effect can be preferably obtained.
[0030] The complex elastic modulus E*(MPa) before wetting with water is preferably 4.0 MPa or more, more preferably 4.5 MPa or more, even more preferably 5.0 MPa or more, particularly preferably 5.4 MPa or more, and most preferably 5.5 MPa or more. It may be 5.9 MPa or more, 6.1 MPa or more, 6.5 MPa or more, 6.7 MPa or more, 7.3 MPa or more, 7.5 MPa or more, 7.8 MPa or more, 7.9 MPa or more, 8.3 MPa or more, 10.2 MPa or more, or 11.0 MPa or more. The upper limit is not particularly limited, but is preferably 20.0 MPa or less, more preferably 17.0 MPa or less, even more preferably 15.2 MPa or less, particularly preferably 15.1 MPa or less, and may be 15.0 MPa or less. When the hardness is within the above range, the effect can be preferably obtained.
[0031] As shown in the above formula (3), the ratio (volume when wetted with water / volume before wetted with water × 100) (volume of rubber composition (after vulcanization) when wetted with water / volume of rubber composition (after vulcanization) before wetted with water × 100) is 99 or more and 100 or less. If the volume before and after wetted with water changes significantly, it will have a negative effect on other physical properties such as abrasion resistance, driving stability, and fuel economy. Therefore, it is important for the tire to maintain a balance of performance by having almost no change in volume before and after wetted with water.
[0032] The change in the complex modulus E* of the rubber composition represented by the above formulas (1) and (2) and the reversible change in the complex modulus E* caused by water can be achieved, for example, by blending a substance capable of reversibly breaking and recombining ionic bonds between rubber molecules by adding water and drying. To be more specific, the change in the complex modulus E* of the rubber composition represented by the above formulas (1) and (2) and the reversible change in the complex modulus E* caused by water can be achieved by using, in combination, a modified BR or modified SBR such as a carboxylic acid modified BR or a carboxylic acid modified SBR, and a compound having a metal, a metalloid or nitrogen. This is because, by using the modified BR or modified SBR in combination, an ionic bond is formed between rubber molecules by a cation derived from a metal, a metalloid or nitrogen and an anion derived from a carboxylic acid, and the ionic bond is broken between rubber molecules by adding water and recombined by drying the water, resulting in a decrease in E* when wet with water and an increase in E* when dry (before wetting with water and after re-drying).
[0033] The E* value when dry (before wetting with water and after re-drying) can be adjusted by the type and amount of chemicals (especially rubber components, fillers, softeners such as oils) compounded in the rubber composition, for example, decreasing the amount of softeners tends to increase the E* value when dry, and increasing the amount of fillers tends to increase the E* value when dry. Also, for example, the E* value when dry can be adjusted by the carboxylic acid modification rate (carboxylic acid group content) of modified BR or modified SBR such as carboxylic acid-modified BR or carboxylic acid-modified SBR, and increasing the carboxylic acid group content tends to increase the E* value when dry.
[0034] The E* when wetted with water can be lowered compared to when dry by, for example, forming a rubber composition crosslinked by ionic bonds in which a part or all of the rubber molecules of the rubber component are crosslinked by ionic bonds, and this allows adjustment of E* when wetted with water. Specifically, by using a modified BR or modified SBR such as carboxylic acid-modified BR or carboxylic acid-modified SBR in combination with a compound having a metal, a metalloid, or nitrogen, a rubber composition crosslinked with ionic bonds is formed, and the E* when wetted with water can be lowered compared to when dry. In addition, it can be adjusted by the type and amount of chemicals (especially rubber components, fillers, softeners such as oils) blended into the rubber composition. For example, increasing the amount of fillers tends to increase E* when wetted with water, and decreasing the amount of softeners tends to increase E* when wetted with water.
[0035] Specifically, by adjusting the E* during drying (before wetting with water, after re-drying) to within a desired range and then using a modified BR or modified SBR such as a carboxylic acid-modified BR or a carboxylic acid-modified SBR in combination with a compound having a metal, a metalloid, or nitrogen, the rubber composition can achieve the E* change represented by the above formulas (1) and (2) and the reversible E* change due to water. Also, the E* before wetting with water described above can be achieved.
[0036] The small volume change of the rubber composition represented by the above formula (3) can also be achieved, for example, by compounding a substance capable of reversibly breaking and recombining the ionic bonds between rubber molecules by the addition and drying of water. Specifically, the small volume change of the rubber composition represented by the above formula (3) can be achieved by using a modified BR or modified SBR such as carboxylic acid-modified BR or carboxylic acid-modified SBR in combination with a compound having a metal element, a metalloid element or a nitrogen element. This is because ionic bonds are formed between rubber molecules by the cations derived from metals, metalloids or nitrogen and the modified BR or modified SBR such as carboxylic acid-modified BR or carboxylic acid-modified SBR, and the cleavage of the ionic bonds between rubber molecules by the addition of water occurs in such a small amount that the absorption of water into the polymer does not affect the volume, and the recombination of the ionic bonds by the drying of water occurs in such a small amount that the dehydration of the polymer does not affect the volume, thereby suppressing the volume change of the rubber composition. Furthermore, even in rubber compositions that do not contain the above-mentioned substances, for example, rubber compositions that contain general-purpose SBR, BR (unmodified SBR, BR, etc.), fillers, etc., the small volume change represented by the above formula (3) can be realized.
[0037] The following describes the drugs that can be used.
[0038] The rubber composition contains SBR and / or BR as a rubber component. In addition, it is preferable that the rubber composition is one in which a part or all of the crosslinks between rubber molecules of the rubber component are crosslinked by ionic bonds. When ionic bonds are included in the crosslinks in the polymer component (rubber component), E* can be reduced only when the material is wetted with water due to the reversibility of the ionic bonds, which are non-covalent bonds. In addition, since ionic bonds are the strongest of all non-covalent bonds, sufficient bonding strength can be maintained when dry.
[0039] In the rubber composition, the proportion of crosslinks consisting of ionic bonds in the total crosslinks (100%) is preferably 0.1% or more, more preferably 0.5% or more, and even more preferably 1% or more. By making it equal to or more than the lower limit, good wet performance and dry performance tend to be obtained. The upper limit is not particularly limited and may be 100%, but is preferably 10% or less, more preferably 5% or less. The proportion of crosslinks consisting of ionic bonds can be measured by the method described in the Examples below.
[0040] The ionic bond between rubber molecules is not particularly limited, and examples thereof include ionic bonds in which the cation side of the ionic bond is derived from at least one selected from the group consisting of metal elements, metalloid elements, and nitrogen elements, and the anion side is derived from at least one selected from the group consisting of carboxylic acid-modified SBR and carboxylic acid-modified BR. Specifically, all combinations of at least one selected from the group consisting of metal elements, metalloid elements, and nitrogen elements and at least one selected from the group consisting of carboxylic acid-modified SBR and carboxylic acid-modified BR are possible, such as a combination of a metal element on the cation side and a carboxylic acid-modified SBR on the anion side, a combination of a metal element on the cation side and a carboxylic acid-modified BR on the anion side, a combination of a metal element on the cation side and a carboxylic acid-modified SBR on the anion side, a combination of a metal element on the cation side and a carboxylic acid-modified BR on the anion side, a combination of a nitrogen element on the cation side and a carboxylic acid-modified SBR on the anion side, and a combination of a nitrogen element on the cation side and a carboxylic acid-modified BR on the anion side.
[0041] Examples of the metal elements on the cation side include alkali metals (lithium, sodium, potassium, etc.), alkaline earth metals (magnesium, calcium, strontium, etc.), etc.; examples of the metalloid elements include silicon, boron, germanium, etc.
[0042] As a compound capable of supplying a metal element, a metalloid element, and a nitrogen element on the cation side of an ionic bond, a compound having at least one selected from the group consisting of a metal element, a metalloid element, and a nitrogen element can be suitably used. In this case, the metal element, the metalloid element, and the nitrogen element in the compound constitute the cation side of the ionic bond. Among them, a compound having a nitrogen element is preferable, and examples thereof include nitrogen element-containing compounds (ammonia, amines, etc.) that can form cations such as quaternary ammonium salts.
[0043] Specific examples of nitrogen-containing compounds (compounds having nitrogen elements) include 1,2-dimethylimidazole, N-butylimidazole, N-(trimethylsilyl)imidazole, N-decyl-2-methylimidazole, N-hydroxyethylimidazole, N-(3-trimethoxysilylpropyl)imidazole, N-vinylimidazole, 1-butylbenzimidazole; trimethylamine, triethylamine, triisopropylamine, tri-n-butylamine, trimethylphosphine, triethylphosphine, triisopropylphosphine, tri-n-butylphosphine, triphenylphosphine; and the like. These may be used alone or in combination of two or more. Among them, imidazole compounds such as N-butylimidazole are preferred.
[0044] The content of the "compound having at least one selected from the group consisting of metal elements, metalloid elements, and nitrogen elements" is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 2 parts by mass or more, particularly preferably 3 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be good. The content of the nitrogen element-containing compound is also preferably in the same range.
[0045] Carboxylic acid-modified SBR and BR on the anion side of the ionic bond include SBR and BR having a carboxylic acid group (carboxyl group). In this case, the carboxylic acid group of the carboxylic acid-modified SBR and BR constitutes the anion side of the ionic bond.
[0046] Carboxylic acid-modified SBR and BR as SBR and BR may be SBR and BR having a carboxylic acid group (carboxyl group), and examples thereof include terminal-modified SBR and BR in which at least one end of SBR or BR is modified with a compound (modifier) having a carboxylic acid group (terminal-modified SBR and BR having a carboxylic acid group at the end), main-chain-modified SBR and BR having a carboxylic acid group in the main chain, main-chain terminal-modified SBR and BR having carboxylic acid groups in the main chain and at the end (for example, main-chain terminal-modified SBR and BR having a carboxylic acid group in the main chain and at least one end modified with a carboxylic acid group), etc. These may be used alone or in combination of two or more kinds.
[0047] The content of "a rubber component having at least one selected from the group consisting of carboxylic acid-modified SBR and carboxylic acid-modified BR" in 100% by mass of the rubber component is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. By making it equal to or more than the lower limit, good wet performance and dry performance tend to be obtained. The upper limit is not particularly limited and may be 100% by mass. The contents of the carboxylic acid-modified SBR and the carboxylic acid-modified BR are also desirably in the same range.
[0048] Examples of other rubber components include diene rubbers such as isoprene rubber, styrene isoprene butadiene rubber (SIBR), acrylonitrile butadiene rubber (NBR), and chloroprene rubber (CR). The rubber components may be used alone or in combination of two or more.
[0049] The rubber composition preferably contains at least one selected from the group consisting of carbon black and silica from the viewpoint of obtaining good effects. In particular, it is preferable that the rubber composition contains silica from the viewpoint of obtaining good wet performance and dry performance. For example, a rubber composition containing a rubber component that satisfies all the above combinations regarding the cation side and the anion side of the ionic bond and at least one selected from the group consisting of carbon black and silica, or a rubber composition containing the rubber component and at least silica can be preferably used.
[0050] The content (total content) of "at least one selected from the group consisting of carbon black and silica" is preferably 1.0 part by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, particularly preferably 30 parts by mass or more, and is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and may be 50 parts by mass or less, or 35 parts by mass or less, based on 100 parts by mass of the rubber component. Within the above range, the effect tends to be favorably obtained.
[0051] Examples of silica include dry silica (anhydrous silicic acid) and wet silica (hydrated silicic acid), among which wet silica is preferred because it has a large number of silanol groups. These may be used alone or in combination of two or more.
[0052] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 60 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 160m 2 / g or more, particularly preferably 170m 2 / g or more. In addition, the N2SA is preferably 600m 2 / g or less, more preferably 300m 2 / g or less, more preferably 250m 2 / g or less, particularly preferably 200m 2 Within the above range, there is a tendency that the effect is favorably obtained. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-81.
[0053] As the silica, for example, products manufactured by Degussa, Rhodia, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Corporation, etc. can be used.
[0054] The content of silica is preferably 1.0 part by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and particularly preferably 30 parts by mass or more, relative to 100 parts by mass of the rubber component, and is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 50 parts by mass or less. Within the above ranges, the effect tends to be excellent.
[0055] When the rubber composition contains silica, it is preferable that the rubber composition further contains a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl- Examples of such silyl compounds include sulfide-based compounds such as N,N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based compounds such as 3-mercaptopropyltrimethoxysilane and 2-mercaptoethyltriethoxysilane; vinyl-based compounds such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based compounds such as 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; glycidoxy-based compounds such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based compounds such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based compounds such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. As commercially available products, for example, products from Degussa, Momentive, Shin-Etsu Silicone Co., Ltd., Tokyo Chemical Industry Co., Ltd., Azumax Co., Ltd., Dow Corning Toray Co., Ltd., etc. can be used. These may be used alone or in combination of two or more kinds.Among these, sulfide-based silane coupling agents and mercapto-based silane coupling agents are preferred because they tend to produce better effects, and disulfide-based silane coupling agents having a disulfide bond, such as bis(3-triethoxysilylpropyl) disulfide, are more preferred.
[0056] The content of the silane coupling agent is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, based on 100 parts by mass of silica. When the content is within the above range, the effect tends to be good.
[0057] As the carbon black, for example, GPF, HAF, ISAF, SAF, etc., which are commonly used in the tire industry, can be used. These may be used alone or in combination of two or more kinds.
[0058] The BET specific surface area of the carbon black is preferably 50 m 2 / g or more, more preferably 100m 2 / g or more, more preferably 110m 2 / g or more, particularly preferably 120m 2 By setting the viscosity at or above the lower limit, sufficient wet performance and abrasion resistance tend to be obtained. The upper limit is preferably 200 m 2 / g or less, more preferably 180m 2 By setting the content to the upper limit or less, good dispersibility and excellent abrasion resistance tend to be obtained. The BET specific surface area of carbon black is a value measured by the BET method in accordance with ASTM D6556.
[0059] The dibutyl phthalate oil absorption (DBP) of carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. By making it equal to or more than the lower limit, sufficient wet performance and abrasion resistance tend to be obtained. In addition, the DBP of carbon black is preferably 220 ml / 100 g or less, more preferably 180 ml / 100 g or less. By making it equal to or less than the upper limit, good dispersibility and excellent abrasion resistance tend to be obtained. The DBP of carbon black is measured in accordance with JIS K6217-4:2001.
[0060] As carbon black, for example, products manufactured by Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Company, etc. can be used.
[0061] The amount of carbon black is preferably 1.0 part by mass or more, more preferably 3.0 parts by mass or more, and even more preferably 5.0 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the rubber component. When the amount is within the above range, the effect tends to be excellent.
[0062] In the rubber composition, the content of silica in the total content of carbon black and silica (100% by mass) is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, particularly preferably 60% by mass or more, and most preferably 80% by mass or more. The upper limit is not particularly limited and may be 100% by mass. Within the above range, the effect tends to be preferably obtained.
[0063] The rubber composition may contain a plasticizer, which is a material that imparts plasticity to the rubber component, and examples of the plasticizer include liquid plasticizers (plasticizers that are in a liquid state at room temperature (25° C.)) and resins (resins that are in a solid state at room temperature (25° C.)).
[0064] The content of the plasticizer (total amount of the plasticizer) is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of the rubber component. The lower limit is not particularly limited and may be 0 parts by mass, but is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and particularly preferably 15 parts by mass or more. Within the above range, the effect tends to be preferably obtained.
[0065] Usable liquid plasticizers (plasticizers that are in a liquid state at room temperature (25° C.)) are not particularly limited, and examples thereof include oils, liquid polymers (liquid resins, liquid diene-based polymers, liquid farnesene-based polymers, etc.), etc. These may be used alone or in combination of two or more kinds.
[0066] The content of the liquid plasticizer is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and further preferably 10 parts by mass or less, based on 100 parts by mass of the rubber component, from the viewpoint of obtaining a good effect, and may not be contained (0 parts by mass). The content of the oil described later is also desirably in the same range (the content of the oil includes the oil contained in the oil extension oil).
[0067] Examples of the oil include process oil, vegetable oil, or a mixture thereof. Examples of the process oil include paraffin-based process oil, aromatic process oil, naphthenic process oil, etc. Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. Among them, process oil (paraffin-based process oil, aromatic process oil, naphthenic process oil, etc.) and vegetable oil are preferred.
[0068] Examples of liquid resins include terpene resins (including terpene phenol resins and aromatic modified terpene resins), rosin resins, styrene resins, C5 resins, C9 resins, C5 / C9 resins, dicyclopentadiene (DCPD) resins, coumarone-indene resins (including coumarone and indene simple resins), phenol resins, olefin resins, polyurethane resins, acrylic resins, etc. Hydrogenated products of these resins can also be used.
[0069] Examples of liquid diene polymers include liquid styrene butadiene copolymers (liquid SBR), liquid butadiene polymers (liquid BR), liquid isoprene polymers (liquid IR), liquid styrene isoprene copolymers (liquid SIR), liquid styrene butadiene styrene block copolymers (liquid SBS block polymers), liquid styrene isoprene styrene block copolymers (liquid SIS block polymers), liquid farnesene polymers, and liquid farnesene butadiene copolymers that are in a liquid state at 25°C. The ends or main chains of these may be modified with polar groups. Hydrogenated versions of these may also be used.
[0070] Examples of the resins that can be used (resins that are in a solid state at room temperature (25°C)) include aromatic vinyl polymers that are in a solid state at room temperature (25°C), coumarone-indene resins, coumarone resins, indene resins, phenolic resins, rosin resins, petroleum resins, terpene resins, and acrylic resins. The resins may be hydrogenated. These may be used alone or in combination of two or more. Of these, aromatic vinyl polymers, petroleum resins, and terpene resins are preferred.
[0071] The content of the resin is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of the rubber component. The lower limit is not particularly limited and may be 0 parts by mass, but is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and particularly preferably 15 parts by mass or more. Within the above range, the effect tends to be preferably obtained.
[0072] The softening point of the resin is preferably 60° C. or higher, more preferably 70° C. or higher, and even more preferably 80° C. or higher. The upper limit is preferably 160° C. or lower, more preferably 130° C. or lower, and even more preferably 115° C. or lower. Within the above range, the effect tends to be favorably obtained. The softening point of the resin is the temperature at which the ball drops when the softening point specified in JIS K6220-1:2001 is measured using a ring and ball softening point tester.
[0073] The aromatic vinyl polymer is a polymer containing an aromatic vinyl monomer as a structural unit. For example, it can be a resin obtained by polymerizing α-methylstyrene and / or styrene, and specifically, it can be a homopolymer of styrene (styrene resin), a homopolymer of α-methylstyrene (α-methylstyrene resin), a copolymer of α-methylstyrene and styrene, a copolymer of styrene and another monomer, etc.
[0074] The coumarone-indene resin is a resin containing coumarone and indene as main monomer components constituting the resin skeleton (main chain). Other monomer components contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.
[0075] The coumarone resin is a resin containing coumarone as a main monomer component constituting the skeleton (main chain) of the resin.
[0076] The indene resin is a resin containing indene as a main monomer component constituting the skeleton (main chain) of the resin.
[0077] The phenolic resin may be a known polymer obtained by reacting phenol with an aldehyde such as formaldehyde, acetaldehyde, or furfural in the presence of an acid or alkali catalyst. Among these, those obtained by reacting with an acid catalyst (such as novolac-type phenolic resin) are preferred.
[0078] Examples of the rosin resin include rosin-based resins such as natural rosin, polymerized rosin, modified rosin, ester compounds thereof, and hydrogenated products thereof.
[0079] Examples of the petroleum resin include C5 resin, C9 resin, C5 / C9 resin, dicyclopentadiene (DCPD) resin, and hydrogenated versions of these resins. Of these, DCPD resin and hydrogenated DCPD resin are preferred.
[0080] The terpene resin is a polymer containing terpene as a constituent unit, and examples thereof include polyterpene resin obtained by polymerizing a terpene compound, and aromatic modified terpene resin obtained by polymerizing a terpene compound and an aromatic compound. As the aromatic modified terpene resin, a terpene phenol resin made from a terpene compound and a phenolic compound, a terpene styrene resin made from a terpene compound and a styrene compound, and a terpene phenol styrene resin made from a terpene compound, a phenolic compound, and a styrene compound can also be used. In addition, examples of the terpene compound include α-pinene, β-pinene, etc., examples of the phenolic compound include phenol, bisphenol A, etc., and examples of the aromatic compound include styrene compounds (styrene, α-methylstyrene, etc.).
[0081] The acrylic resin is a polymer containing an acrylic monomer as a constituent unit. For example, a styrene-acrylic resin having a carboxyl group and obtained by copolymerizing an aromatic vinyl monomer component and an acrylic monomer component, such as a styrene-acrylic resin, can be used. Among them, a solventless carboxyl group-containing styrene-acrylic resin can be preferably used.
[0082] Examples of commercially available plasticizers that can be used include products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Corporation, Orisoi Corporation, H&R Corporation, Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., Nisshin Oillio Group Ltd., Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nitto Chemical Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.
[0083] The rubber composition may contain a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more. Among them, petroleum waxes are preferred, and paraffin wax is more preferred.
[0084] As the wax, for example, products available from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. can be used.
[0085] When the wax is contained, the content thereof is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the rubber component. The rubber composition may not contain wax.
[0086] The rubber composition may contain an antioxidant. Examples of the antioxidant include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Examples of the antioxidant include p-phenylenediamine antioxidants such as quinolinone; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These antioxidants may be used alone or in combination of two or more. Among them, p-phenylenediamine antioxidants and quinoline antioxidants are preferred.
[0087] As the antioxidant, for example, products available from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Industry Co., Ltd., Flexis, etc. can be used.
[0088] When an antioxidant is contained, the content thereof is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component. The rubber composition may not contain an antioxidant.
[0089] The rubber composition may contain stearic acid. As the stearic acid, any conventionally known product can be used, for example, products available from NOF Corporation, NOF Corporation, Kao Corporation, Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.
[0090] When stearic acid is contained, the content thereof is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component. The rubber composition may not contain stearic acid.
[0091] The rubber composition may contain zinc oxide. As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.
[0092] When zinc oxide is contained, the content is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the rubber component. When the content is within the above range, the effect tends to be better. The rubber composition may not contain zinc oxide.
[0093] The rubber composition may contain sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. These may be used alone or in combination of two or more kinds.
[0094] As sulfur, for example, products from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanritsu Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. can be used.
[0095] When sulfur is contained, the content thereof is preferably 0.1 part by mass or more, more preferably 0.5 part by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 3 parts by mass or less, based on 100 parts by mass of the rubber component. The rubber composition may not contain sulfur.
[0096] The rubber composition may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenyl guanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide vulcanization accelerators and guanidine vulcanization accelerators are preferred because they provide more suitable effects.
[0097] As the vulcanization accelerator, for example, products manufactured by Kawaguchi Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., etc. can be used.
[0098] When the vulcanization accelerator is contained, the content thereof is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 7 parts by mass or less, based on 100 parts by mass of the rubber component. The rubber composition may not contain a vulcanization accelerator.
[0099] In order to obtain the desired effect, it is preferable that the content (parts by mass) of the silica per 100 parts by mass of the rubber component and the content (parts by mass) of the plasticizer per 100 parts by mass of the rubber component satisfy the following formula: Plasticizer content / Silica content<1.0 The plasticizer content / silica content is preferably 0.9 or less, more preferably 0.8 or less, even more preferably 0.7 or less, and particularly preferably 0.6 or less. The lower limit is not particularly limited, but is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.4 or more. By setting the lower limit within the above range, the effect tends to be preferably obtained.
[0100] From the viewpoint of obtaining the desired effect, it is preferable that the content (parts by mass) of the silica per 100 parts by mass of the rubber component and the content (parts by mass) of the resin (a resin in a solid state at room temperature (25° C.)) per 100 parts by mass of the rubber component satisfy the following formula: Resin content / Silica content<1.0 The resin content / silica content is preferably 0.9 or less, more preferably 0.8 or less, even more preferably 0.7 or less, and particularly preferably 0.6 or less. The lower limit is not particularly limited, but is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.4 or more. By setting the lower limit within the above range, the effect tends to be preferably obtained.
[0101] In addition to the above components, the rubber composition may further contain additives commonly used in the tire industry, such as organic peroxides, fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, and mica. The content of these additives is preferably 0.1 to 200 parts by mass per 100 parts by mass of the rubber component. The rubber composition may not contain these additives.
[0102] The rubber composition can be produced, for example, by kneading the components using a rubber kneading device such as an open roll or a Banbury mixer, and then vulcanizing the mixture.
[0103] As for the kneading conditions, in the base kneading step in which additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or lower, preferably 80 to 110°C. Furthermore, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 140 to 190°C, preferably 150 to 185°C. The vulcanization time is usually 5 to 15 minutes.
[0104] The rubber composition can be used for tire components (as a rubber composition for tires) such as tread (cap tread), sidewall, base tread, under tread, shoulder, clinch, bead apex, breaker cushion rubber, carcass cord covering rubber, insulation, chafer, inner liner, etc., and side reinforcing layer of run-flat tires. In particular, it can be suitably used for tire tread, shoulder, and especially cap tread because it can suppress the change in grip performance when changing from a dry road surface to a wet road surface. In addition, it can be suitably used for sidewall because it improves steering stability on wet roads.
[0105] The tire (pneumatic tire, etc.) of the present invention is manufactured by a normal method using the above rubber composition. That is, the rubber composition, which contains various additives as necessary, is extruded in an unvulcanized state to match the shapes of each tire component (tread, sidewall, etc.), molded in a tire building machine by a normal method, and laminated together with other tire components to form an unvulcanized tire, which is then heated and pressurized in a vulcanizer to manufacture the tire.
[0106] At least a part of the tire components (tread, sidewall, etc.) of the tire may be made of the rubber composition, and the entire tire components may be made of the rubber composition.
[0107] The above tires are suitably used as passenger car tires, large passenger car tires, large SUV tires, truck and bus tires, motorcycle tires, racing tires, studless tires (winter tires), all-season tires, run-flat tires, aircraft tires, mining tires, etc. EXAMPLES
[0108] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0109] Various chemicals used in the examples and comparative examples will be collectively described below. Carboxylic acid modified BR: Nanoprene B M750H VP manufactured by LANXESS Carboxylic acid modified SBR: Nipol LX426 (styrene-butadiene latex, rubber solids 50%) manufactured by Zeon Corporation The carboxylic acid-modified SBR used was coagulated rubber made by subjecting Nipol LX426 to the following process. Weigh out 12 kg of Equinene (a mixed solvent whose main component is alcohol) into a 1.25 L bucket and stir mechanically. 2. Weigh out 6.5 kg of emulsion (Nipol LX426) and pour into 1. 3. Weigh out 1.5 kg of 0.5% aqueous sulfuric acid solution and pour it into 2. 4. Filter through a colander (approximately 6.5 kg of WET polymer). 5. Blow dry in a walk-in draft. 6. Dry in a vacuum oven until the loss on drying is 0.5% (approximately 3.1 kg of dry polymer). BR: BR150B manufactured by Ube Industries, Ltd. SBR: Nipol 1502 (E-SBR) manufactured by ZEON Co., Ltd. 1,2-Dimethylimidazole: Curesol 1.2DMZ manufactured by Shikoku Kasei Co., Ltd. 1-Butylimidazole: Commercially available Silica 1: Ultrasil VN3 (N2SA175m) manufactured by Evonik Degussa 2 / g) Silica 2: Evonik Degussa 9000GR (N2SA235m 2 / g) Carbon black: SEAT 9H manufactured by Tokai Carbon Co., Ltd. (DBP oil absorption: 115 ml / g, BET specific surface area: 110 m 2 / g) Resin: SYLVARES SA85 manufactured by Arizona Chemical (copolymer of α-methylstyrene and styrene, Tg 43°C, softening point 85°C) Stearic acid: NOF Corporation's "Tsubaki" stearic acid Zinc oxide: Two types of zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. Vulcanization accelerator 1: Noccela NS (N-tert-butyl-2-benzothiazylsulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: Noccelaer D (1,3-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd.
[0110] Examples and Comparative Examples According to the compounding recipes shown in each table, chemicals other than sulfur and vulcanization accelerator were kneaded for 4 minutes at 160°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 4 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized at 170° C. for 12 minutes to obtain a vulcanized rubber composition. In addition, the obtained unvulcanized rubber composition was molded into a tread shape and laminated together with other tire components on a tire building machine to form an unvulcanized tire, which was then vulcanized at 170°C for 12 minutes to produce a test tire (size: 195 / 65R15). The reference comparative example in Table 1 is Comparative Example 1-1, and the reference comparative example in Table 3 is Comparative Example 3-1. The reference comparative examples in Table 2 are Comparative Example 2-2 for wet grip performance, Comparative Example 2-4 for dry grip performance, and Comparative Example 2-1 for fuel economy.
[0111] The obtained vulcanized rubber compositions and test tires were evaluated as follows, and the results are shown in the tables.
[0112] <Complex elastic modulus E* measurement> The complex elastic modulus E* of the rubber piece (vulcanized rubber composition) was measured using RSA-GII manufactured by TA Instruments (the value of E* is the average value of five measurements). (Measurement conditions) Measurement mode: Extension Frequency: 10Hz Distortion: 0.25% ·Temperature: 23℃ Sample size: L10mm x W3mm x T0.5mm (L is the distance between the chucks)
[0113] (Complex modulus E* before wetting with water) The vulcanized rubber composition of the above sample size was dried under normal temperature and pressure conditions until it reached a constant weight. The complex modulus E* of the obtained vulcanized rubber composition (rubber piece) before wetting with water was measured by the above method, and this was taken as E* before wetting with water.
[0114] (Complex modulus E* when wet with water) The vulcanized rubber composition of the above sample size was immersed in 100 ml of water at 23° C. for 2 hours to obtain a vulcanized rubber composition when wet with water. The complex modulus E* of the obtained vulcanized rubber composition (rubber piece) when wet with water was measured by the above method and was defined as E* when wet with water.
[0115] (Complex modulus E* after drying) The vulcanized rubber composition after wetting with water was dried under normal temperature and pressure conditions until it reached a constant weight, to obtain a vulcanized rubber composition after drying with water. The temperature of the obtained vulcanized rubber composition after drying with water was returned to 23°C, and the complex modulus E* of the dried vulcanized rubber composition (rubber piece) was measured by the above method, and this was defined as E* after drying with water.
[0116] <Volume change measurement> Using a Leica M205C stereomicroscope, the volume of a rectangular parallelepiped piece of rubber (a rectangular parallelepiped shape of 30.0 mm length × 30.0 mm width × 0.50 mm thickness) was measured (measurement temperature 23°C). Regarding the volume before wetting with water, the rectangular rubber piece was dried under normal temperature and pressure conditions until it reached a constant weight, and then the temperature of the obtained vulcanized rubber composition was adjusted to 23°C, and the volume of the vulcanized rubber composition before wetting with water was measured by the method described above (volume before wetting with water). The rectangular rubber piece was immersed in 100 ml of water at 23°C for 2 hours to obtain a vulcanized rubber composition when wet with water. The obtained vulcanized rubber composition was then adjusted to 23°C, and the volume of the vulcanized rubber composition when wet with water was measured using the method described above (volume when wet with water).
[0117] (Wet grip performance) Each test tire was fitted to all wheels of a vehicle (domestic FF 2000cc), and the braking distance from an initial speed of 100km / h on a wet asphalt road surface was measured. The braking distance of the reference comparative example was set to 100, and each compound was expressed as an index. The higher the index, the better the wet grip performance.
[0118] (Dry grip performance) Each test tire was fitted to all wheels of a vehicle (domestic FF 2000cc), and the braking distance from an initial speed of 100km / h on a dry asphalt road surface was measured. The braking distance of the reference comparative example was set to 100, and each compound was expressed as an index. The higher the index, the better the dry grip performance. An index of 97 or more is acceptable for practical use.
[0119] (Fuel efficiency (rolling resistance)) Using a rolling resistance tester, the rolling resistance was measured when the test tire was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and was expressed as an index with the reference comparative example being 100. The higher the index, the better the fuel efficiency on dry roads. An index of 85 or higher is acceptable for practical use.
[0120] [Table 1]
[0121] [Table 2]
[0122] [Table 3]
[0123] In each table, the overall performance can be evaluated by adding up two or more indices of wet grip performance (wet performance), dry grip performance (dry performance), and fuel efficiency (for example, in the case of the overall performance of wet performance and dry performance, the sum of the indices of wet grip performance and dry grip performance is used, and in the case of the overall performance of wet performance, dry performance, and fuel efficiency, the sum of the indices of wet grip performance, dry grip performance, and fuel efficiency is used). The complex modulus E* changes reversibly depending on water, and the examples that satisfied the above formulas (1) to (3) were excellent in the overall performance.
Claims
1. butadiene rubber and / or styrene butadiene rubber, The rubber composition contains at least one selected from the group consisting of carbon black and silica in an amount of 1.0 part by mass or more per 100 parts by mass of the rubber component, and A rubber composition whose complex modulus E* is reversibly changed by water and which satisfies the following formulas (1) to (3): Formula (1) Complex elastic modulus E* when wetted with water / Complex elastic modulus E* before wetted with water×100≦98 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (2) 99≦Complex elastic modulus E* after drying / Complex elastic modulus E* before wetting with water×100≦100 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (3) 99≦volume when wetted with water / volume before wetted with water×100≦100 (In the formula, the volume is the volume of the rubber composition at 23° C.)
2. butadiene rubber and / or styrene butadiene rubber, The rubber composition contains 15 to 70 parts by mass of silica per 100 parts by mass of the rubber component, and A rubber composition whose complex modulus E* is reversibly changed by water and which satisfies the following formulas (1) to (3): Formula (1) Complex elastic modulus E* when wetted with water / Complex elastic modulus E* before wetted with water×100≦98 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (2) 99≦Complex elastic modulus E* after drying / Complex elastic modulus E* before wetting with water×100≦100 (In the formula, E* is the E* of the rubber composition at 23°C.) Formula (3) 99≦volume when wetted with water / volume before wetted with water×100≦100 (In the formula, the volume is the volume of the rubber composition at 23° C.)
3. 3. The rubber composition according to claim 1, wherein the rubber molecules of the rubber component are partially or entirely crosslinked by ionic bonds.
4. 4. The rubber composition according to claim 2, further comprising 1.0 part by mass or more of at least one selected from the group consisting of carbon black and silica, based on 100 parts by mass of the rubber component.
5. The rubber composition according to any one of claims 1, 3 and 4, comprising 15 to 70 parts by mass of silica per 100 parts by mass of the rubber component.
6. The rubber composition according to any one of claims 1 to 5, comprising at least one selected from the group consisting of carboxylic acid-modified styrene-butadiene rubber and carboxylic acid-modified butadiene rubber, and a compound having at least one selected from the group consisting of a metal element, a semi-metal element, and a nitrogen element.
7. The rubber composition according to any one of claims 1 to 6, comprising 1 to 50 parts by mass of a resin per 100 parts by mass of the rubber component.
8. The rubber composition according to any one of claims 1 to 7, comprising 15 parts by mass or more of a plasticizer per 100 parts by mass of the rubber component.
9. The rubber composition according to any one of claims 1 to 8, wherein the contents of silica and plasticizer per 100 parts by mass of the rubber component satisfy the following formula: Plasticizer content / Silica content < 1.0
10. The rubber composition according to any one of claims 1 to 9, wherein the contents of silica and resin per 100 parts by mass of the rubber component satisfy the following formula: Resin content / Silica content < 1.0
11. The rubber composition according to any one of claims 1 to 10, which is a rubber composition for treads.
12. A tire having a tire component at least partially constituted by the rubber composition according to any one of claims 1 to 11, The tire component is a tread.
Citation Information
Patent Citations
Tread rubber composition
JP1996151482A
Rubber composition for tire tread and pneumatic tire composed of the same
JP2006124423A
Rubber composition and pneumatic tire using the same
JP2007321126A
Rubber composition for tire tread and pneumatic tire
JP2008285524A
Rubber composition for tire and pneumatic tire
JP2013100449A